A Grassroots Effort to Renew the Schoolyard: The Learning Garden - Kingery-Page, Katie; Hunt, John D.; Teener, Linda (My University, 2011)
Like thousands of schools across the United States, Northview Elementary School in Manhattan, Kansas plans to infuse kids’ lives with nature. Educators, community advocates, and parents gathered funds, drew plans, and constructed a learning garden because they saw its potential to affect students. This paper documents the case of Northview and reviews research relevant to the establishment and success of schoolyard gardens.
Keywords: Schoolyard gardens; Elementary schools; Hands-on learning; Grassroots development